From resilience to revolution : how foreign interventions destabilize the Middle East - Yom, Sean L. (Columbia studies in Middle East politics., 2016)
As colonial rule dissolved in the 1930s and 1950s, Middle Eastern autocrats constructed new political states to solidify their reigns, with varying results. Some proved durable despite economic challenges and devastating wars, such as the Sabah regime of Kuwait, which faced little opposition and enjoyed mass support. Others such as the Hashemite monarchy of Jordan barely survived the twentieth century, tested repeatedly by uprisings from within and pressures from beyond. Still others were deposed through revolutionary upheavals as popular forces mobilized to overthrow their despotic reign, as with the Pahlavi dynasty of Iran. Why did equally ambitious authoritarians meet such unequal fates' Sean L. Yom makes a bold, singular claim: the durability of Middle Eastern regimes stems from their geopolitical origins. At the dawn of the postcolonial era, many autocratic states across the region had little support from their own societies and struggled to overcome widespread opposition. When foreign powers intervened to prop these regimes up, they unwittingly sabotaged the prospects for long-term stability by discouraging triumphant leaders from reaching out to their people and bargaining for mass support-early coalitional decisions that created repressive institutions and planted the seeds for future unrest. Only when they were secluded from larger geopolitical machinations did Middle Eastern regimes come to grips with their weaknesses and build broader coalitions. Based on comparative historical analyses of Iran, Jordan, and Kuwait, Yom examines the foreign interventions, coalitional choices, and state outcomes that characterize the modern Middle East. A key text for foreign policy scholars, From Resilience to Revolution shows how outside interference can corrupt the most basic choices of governance: who to reward, who to punish, who to compensate, and who to manipulate.